2019
DOI: 10.1177/1362361318822498
|View full text |Cite
|
Sign up to set email alerts
|

It’s the fear of the unknown: Transition from higher education for young autistic adults

Abstract: More young people with a diagnosis of autism are enrolling and successfully completing higher education courses than ever before and this is set to increase; however, while there is a burgeoning body of literature surrounding the transition into this stage of education, there is a paucity of research that investigates the transition as this population exit higher education. This exploratory qualitative study is one of the first to identify the specific experiences of young autistic adults making this transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 59 publications
1
26
0
Order By: Relevance
“…Our study contributes to the existing literature related to post-secondary transition for individuals with autism (e.g. Cashin 2018;Elias and White 2018;Lambe et al 2019;Vincent 2019Vincent , 2020 by widening the perspective to specifically include students' and graduates' perceptions about employment support related to the transition from university to work. We discovered that the support within university structures was not meeting students' individual needs and that caring relationships were the most favourable supporting factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study contributes to the existing literature related to post-secondary transition for individuals with autism (e.g. Cashin 2018;Elias and White 2018;Lambe et al 2019;Vincent 2019Vincent , 2020 by widening the perspective to specifically include students' and graduates' perceptions about employment support related to the transition from university to work. We discovered that the support within university structures was not meeting students' individual needs and that caring relationships were the most favourable supporting factors.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the transition into university and the time at university have been explored, little research related to the transition from university into employment has been undertaken. This period often causes anxiety for those with autism, but it can also be perceived as a positive departure and a moment for identity development when entering adulthood (Vincent 2019). A systematic review by Cashin (2018) found four studies that consisted of a case study, discussion papers, and one UK-based study (Van Hees, Moyson, and Roeyers 2015;MacLeod and Green 2009;Martin 2006Martin , 2007.…”
Section: Autism and Support At Universitymentioning
confidence: 99%
“…Participants could view the questions before the interview; 10 participants elected to do so. Different modes of communication were offered (as detailed below) to allow flexibility and cater for diverse communication preferences ( Vincent, 2019 ). Interviews were arranged at a convenient time in the preferred mode – seven participants completed the interview over the phone, Skype or in person, two used instant messaging on Skype and five used email.…”
Section: Methodsmentioning
confidence: 99%
“…Fortunately, more recently there has been increasing recognition that it is time for change, with autistic advocates, academics and activists insisting that participatory research is the way forward (e.g., Pellicano and Stears, 2011;Milton and Bracher, 2013;Fletcher-Watson et al, 2019;Gowen et al, 2019). Indeed, there are some great examples emerging of collaborations that have involved the autism community in priority-setting and research (e.g., Nicolaidis et al, 2011Nicolaidis et al, , 2013Bertilsdotter Rosqvist, 2019;Crane et al, 2019;Fletcher-Watson et al, 2019;Vincent, 2019;Young et al, 2019;Pavlopoulou, 2020;Pellicano et al, 2020). One gold-standard example of how researchers, autistic people and their allies can effectively collaborate is the "Shaping Autism Research" seminar series (Fletcher-Watson et al, 2019).…”
Section: A Brighter Futurementioning
confidence: 99%